P2_2 Playing at a stadium one mile above sea level - Gorley, Michael; Anand, Jassdeep; Buccheri, Alex; Waever, Iain (Physics Special Topics, 2009)
<span style="font-size: 10pt; font-family: ";Calibri";,";sans-serif";; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">This paper focuses on the decrease in the performance of professional athletes at high altitude; the central interest is the proportional drop in performance to partial pressure of oxygen in the atmosphere. Too little data has been scientifically recorded to make any accurate functional predictions as to the detriment in performance with altitude, while <span style="font-size: 10pt; font-family: ";Calibri";,";sans-serif";; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">inductive interpretation of the available data would lead to the prediction that there is an effect no <span style="font-size: 10pt; font-family: ";Calibri";,";sans-serif";; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">quantifiable predictions to advantage of having a home stadium at high altitude is possible